Efek Media dan Pengadilan Opini - Malau, Ruth (Universitas Semarang, 2013)
Countries that embrace the ideology of freedom of the press, the court is of opinion that is commonly encountered in public spaces. Media, in this case could be interpreted as a medium in favor of the public interest which requires the presence of a new color in Libyan politics for 42 years filled with pressure and persecution.Revolutionary period which lasted for most of the year 2011, which then shows how the media have spread the legality of its influence over public opinion. The mass media in Indonesia does have the power to set the political agenda, because democracy gives him legal to do so.However, court opinions that appeared in the Libyan revolution is not because the country embraced the ideology of freedom of the press, but because of the pull-menaraik between freedom of the press with dimensions embedded control during the reign of Gaddafi.